Comparative study of helium bubble formation in Cr-Fe-Ni-Mn high-entropy alloy and 18Cr10NiTi steel after irradiation and post-irradiation annealing - Kalchenko, А.S.; Karpov, S.A.; Kopanets, I.E.; Tikhonovsky, M.A.; Tolstolutskaya, G.D. (Вопросы атомной науки и техники, 2019)
High entropy alloys (HEAs) are considered for applications in nuclear reactors due to their promising mechanical properties, corrosion and radiation resistance. In order to understand the irradiation effects in HEAs and to demonstrate their potential advantages over conventional austenitic stainless steels, we performed helium ion irradiation experiments with 20Cr-40Fe-20Ni-20Mn high-entropy alloy and 18Cr10NiTi steel under an identical condition. Both alloys have been irradiated to a dose of 4.8 displacement per atom (dpa) and a helium concentration of 11.7 at.% at room temperature. After subsequent annealing at 500°C the microstructure evolution of irradiated materials was examined. The irradiation promotes the formation of a high density of bubbles in HEA and steel. Comparison of parameters of helium porosity in these materials has been done. Високоентропійні сплави (ВЕС) розглядаються як перспективні матеріали для застосування в ядерних реакторах через їх багатообіцяючі механічні властивості, корозійну та радіаційну стійкість. З метою розуміння впливу опромінення на властивості ВЕС і демонстрації їх потенційних переваг у порівнянні зі звичайними аустенітними нержавіючими сталями ми провели експерименти з опромінення в ідентичних умовах іонами гелію з енергією 20 кеВ ВЕС 20Cr-40Fe-20Ni-20Mn і стали Х18Н10Т. Сплави були опромінені при кімнатній температурі до дози 4,8 зміщення на атом (зна) і концентрації гелію 11,7 ат.%. Еволюцію мікроструктури опромінених матеріалів досліджували після відпалу при 500°С. Опромінення і відпал призвели до створення високої щільності бульбашок у ВЕС і сталі. Проведено порівняння параметрів гелієвої пористості в цих матеріалах. Высокоэнтропийные сплавы (ВЭС) рассматриваются как перспективные материалы для применения в ядерных реакторах из-за их многообещающих механических свойств, коррозионной и радиационной стойкости. С целью понимания влияния облучения на свойства ВЭС и демонстрации их потенциальных преимуществ по сравнению с обычными аустенитными нержавеющими сталями мы провели эксперименты по облучению в идентичных условиях ионами гелия с энергией 20 кэВ ВЭС 20Cr-40Fe-20Ni-20Mn и стали Х18Н10Т. Оба сплава были облучены при комнатной температуре до дозы 4,8 смещения на атом (сна) и концентрации гелия 11,7 ат.%. Эволюцию микроструктуры облученных материалов исследовали после отжига при 500°С. Облучение и отжиг привели к образованию высокой плотности пузырьков в ВЭС и стали. Проведено сравнение параметров гелиевой пористости в этих материалах.